All Days 2007
DOI: 10.4043/18691-ms
|View full text |Cite
|
Sign up to set email alerts
|

Sand Transport Modeling in Multiphase Pipelines

Abstract: Prediction of the critical flow rate that will result in sand bed formation in multiphase flow is a critical aspect of multiphase production. Many correlations have been developed for solids transportation in multiphase flow; however, all of them treat the multiphase flow in an ad hoc way that does not respect the complexity of the phenomenon. Further, many approaches rely on correlations that have been developed for much higher solids loading than would occur in oil and gas production. In this paper, first a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 0 publications
1
51
0
Order By: Relevance
“…In contrast, for 0.1 meter inclined pipe where slug flow developed there was enhanced solid transportation in the pipe which resulted in lower sand hold up. This phenomenon was also observed by previous investigators such as [3,10]. Figures 6&7 shows the results of the experiments on the effects of flow patterns on sand particle transport velocity profiles in horizontal & inclined test pipe sections for water-oil-gas-sand flow systems.…”
Section: Effect Of Gas Injection On Mtvsupporting
confidence: 60%
See 1 more Smart Citation
“…In contrast, for 0.1 meter inclined pipe where slug flow developed there was enhanced solid transportation in the pipe which resulted in lower sand hold up. This phenomenon was also observed by previous investigators such as [3,10]. Figures 6&7 shows the results of the experiments on the effects of flow patterns on sand particle transport velocity profiles in horizontal & inclined test pipe sections for water-oil-gas-sand flow systems.…”
Section: Effect Of Gas Injection On Mtvsupporting
confidence: 60%
“…The characterisation are often achieved by direct visual observation, video recording or with the aid of acoustic sand detection [3,[5][6][7][8]. The classifications of sand flow patterns reported in the literatures by other researchers are similar and can be distinctly classified as follows, [9,10]  Homogeneous suspension: Sand is transported in suspension and distributed uniformly inside the pipe.  Suspension/Saltation: Sand is still transported in suspension but it is densely populated near the low-side wall so that it is virtually transported by jumping forward or saltating on the surface of the low-side pipe wall.…”
Section: Introductionmentioning
confidence: 98%
“…Critical velocity was defined as the liquid velocity required to prevent a sand bed from forming. A model for sand transport in multiphase flow was proposed by Angelsen et al, in 1989. They extended the sand transport model that they proposed to multiphase flow by using actual liquid velocity and hydraulic pipe diameter in the single-phase flow model.…”
Section: Literature Reviewmentioning
confidence: 98%
“…They extended the sand transport model that they proposed to multiphase flow by using actual liquid velocity and hydraulic pipe diameter in the single-phase flow model. Critical velocity was defined as the liquid velocity required to prevent a sand bed from forming in that study (Angelsen et al, 1989). In 2000, a model for both single-phase and two-phase flows was developed by simplifying the previous work of Wicks, Holte, and Oroskar and Turian (Salama, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The dip couples the effects of the downhill and uphill sections forming a complex pipe geometry which strongly affects sand transport characteristics differently from those in horizontal, downward and upward inclined pipes [16]. Studies by Al-lababidi et al [7] and Danielson [2] showed that sand transport velocity and sand hold-up in liquid-sand flow in -1. [17] found in their experimental study that V-inclined pipe with small gradient ( 1 6 of a typical representative of gradient on seabed have significant effect on sand mobility in the three sections of the V-pipe.…”
Section: Introductionmentioning
confidence: 99%